Investigation and assessment of nutritional status among Chinese elite artistic swimming athletes - Li, L.; Xu, J.; Fang, H.; Wang, X. (Exercise Biochemistry Review, 2018)
Objective The sport of artistic swimming is unique which requires a mixture of endurance, power, acrobatics, flexibility, and eurhythmics to produce an artistic performance. Optimal nutrition plays an important role in attaining high level of achievements for artistic swimming athletes, a poor nutritional status will significantly affect their health, athletic performance and post-exercise recovery. However, the assessment of nutritional status among artistic swimming athletes is very lack. The purpose of present study was to assess the nutritional status of Chinese elite artistic swimming athletes and provide suggestions for them to modify their dietary structures. Methods During the summer training season before the 17th FINA World Championships, 17 Chinese elite artistic swimming female athletes participated in this study. After an overnight fast, the anthropometric data including height, weight, BMI, body fat percentage (BF%), and waist/hip ratio were collected in the early morning around 7 a.m. before breakfast. The 24 hours dietary recall was used to collect dietary intake data of individuals, the athletes were required to record their daily dietary intake in the structured questionnaire for 2 work days and 1 weekend day. During data processing, the cooked foods were converted into raw amounts of each food material by standardized recipe method, and the nutritive value was calculated by using a dietary nutrients analysis software.